United States V. Alvarez Machain syllabus : certiorari to the United States Court of appeals for the ninth circuit - (:unkn) unknown (Universidad Panamericana. Facultad de Derecho, 1993)
Responded, a citizen resident of Mexico, was forcibily kidnapped from his home and flown by private plane to Texas arrested for his participation in the kidnapping and murder of a Drug Enforcement Administration DEA agent and the agent's pilot.
Derecho
Keywords: Extradición; Tratados internacionales; CIENCIAS SOCIALES